Answer:
[tex]x = \frac{1}{3} [/tex]
Step-by-step explanation:
*Move terms to the left and set equal to zero:
4㏒(√x) - ㏒(3x) - ㏒(x²) = 0
*simplify each term:
㏒(x²) - ㏒(3x) - ㏒(x²)
㏒(x²÷x²) -㏒(3x)
㏒(x²÷x² / 3x)
*cancel common factor x²:
㏒([tex]\frac{1}{3x}[/tex])
*rewrite to solve for x :
10⁰ = [tex]\frac{1}{3x}[/tex]
1 = [tex]\frac{1}{3x}[/tex]
1 · x = [tex]\frac{1}{3x}[/tex] · x
1x = [tex]\frac{1}{3}[/tex]
*that would be our answer, however, the convention is to exclude the "1" in front of variables so we are left with:
x = [tex]\frac{1}{3}[/tex]